2003
DOI: 10.1086/378720
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy Type 2: Human Founder Haplotype and Evolutionary Conservation of the Repeat Tract

Abstract: Myotonic dystrophy (DM), the most common form of muscular dystrophy in adults, can be caused by a mutation on either chromosome 19 (DM1) or 3 (DM2). In 2001, we demonstrated that DM2 is caused by a CCTG expansion in intron 1 of the zinc finger protein 9 (ZNF9) gene. To investigate the ancestral origins of the DM2 expansion, we compared haplotypes for 71 families with genetically confirmed DM2, using 19 short tandem repeat markers that we developed that flank the repeat tract. All of the families are white, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
71
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 25 publications
5
71
1
4
Order By: Relevance
“…As described by Liquori et al [11], alleles displaying an uninterrupted stretch of 20 CCTG can be valued as premutational. Indeed, the repeat that was found in patients 1 and 2 by cloning comprised 32 succeeding CCTG without interruption.…”
Section: Discussionmentioning
confidence: 98%
“…As described by Liquori et al [11], alleles displaying an uninterrupted stretch of 20 CCTG can be valued as premutational. Indeed, the repeat that was found in patients 1 and 2 by cloning comprised 32 succeeding CCTG without interruption.…”
Section: Discussionmentioning
confidence: 98%
“…The number of CCTG repeats is o30 in the normal allele, with interruptions by GCTG and/or TCTG motifs, and this allele is stably transmitted from one generation to the next. 1,3 However, in the expanded allele only the CCTG tract elongates and no GCTG and TCTG interruptions occur. The expanded ZNF9 allele is extremely unstable and the size is highly variable, ranging from 75 to 11 000 repeats, with a mean of 5000 CCTG repeats.…”
mentioning
confidence: 99%
“…4 To date, DM2 mutations have been identified predominantly in European Caucasians. 3,5 Although a small number of DM2 mutations have been reported in non-European populations, including families in Morocco, Algeria, Lebanon, Afghanistan and Sri Lanka, 6,7 all reported that DM2 patients had been considered to originate from a single common founder because they shared an identical haplotype. 3,5,7 However, in 2008 we identified the first case of DM2 in an East-Asian population, in a Japanese patient with a disease haplotype distinct from that shared among Caucasians, indicating that DM2 exists in non-Caucasian populations and that there may have been separate founders.…”
mentioning
confidence: 99%
See 2 more Smart Citations